2014
DOI: 10.1111/cas.12319
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD56 is an unfavorable prognostic factor for acute promyelocytic leukemia with higher initial white blood cell counts

Abstract: Expression of CD56 has recently been introduced as one of the adverse prognostic factors in acute promyelocytic leukemia (APL). However, the clinical significance of CD56 antigen in APL has not been well elucidated. We assessed the clinical significance of CD56 antigen in 239 APL patients prospectively treated with all-trans retinoic acid and chemotherapy according to the Japan Adult Leukemia Study Group APL97 protocol. All patients were prospectively treated by the Japan Adult Leukemia Study Group APL97 proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
4
18
1
1
Order By: Relevance
“…Several studies have reported the unfavorable effect of CD56 expression in the ATRA and chemotherapy-based therapy [22][23][24][25][26][27]. We have found the incidence of CD56 expression to be 15.9%.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies have reported the unfavorable effect of CD56 expression in the ATRA and chemotherapy-based therapy [22][23][24][25][26][27]. We have found the incidence of CD56 expression to be 15.9%.…”
Section: Discussionmentioning
confidence: 51%
“…Исследование позволило выявить очевидную иммунофенотипическую гетерогенность среди пациентов этой группы: выявлены разные профили коэкспрессирующихся маркеров и уровни их экспрессии. В более ранних исследованиях ETP-ОЛЛ считали подтипом исключительно TI-ОЛЛ, позже эти данные были опровергнуты [21,22]. Мы тоже обнаружили различные варианты Т-ОЛЛ, которые удовлетворяют иммунофенотипическим критериям ETP-ОЛЛ (рисунки 3-7).…”
Section: обсуждение результатов исследованияunclassified
“…It is present in most natural killer cells and in some T cells that take part in cancer cell lysis. CD56 is proposed to be an unfavorable prognostic factor in leukemia [18] and is used as a neuroendocrine tumor marker [19].…”
Section: Introductionmentioning
confidence: 99%